E-Money sebagai Instrument Pembayaran Micro Payment Dalam Perspektif Maqashid Syariah - Siti Khozinatun Niam; Muhammad Haris Hidayatulloh (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The current rapid development of technology has penetrated all aspects, including financial institutions with the existence of e-money digital financial services. The use of E-money as a payment system has shifted payment methods from cash to non-cash by the general public and Muslims. Then it is necessary to carry out a sharia review related to the use of e-money regarding the mechanism for using e-money, the contract used, and a review of sharia maqasyid. The type of research used is library research using descriptive analysis techniques. The results of the Electronic Money Transaction Mechanism (e-money), namely the operator can only be carried out by the issuer himself or another party, the operator who provides the infrastructure for its implementation. This then provides security guarantees for its users in transactions. Electronic money (e-money) in mashed shari'ah. guaranteed security, and guaranteed halal in the transaction. The contract is used in Electronic Money (e-money). Sales Purchase Agreement, Wadi'ah Agreement, and Ijarah Agreement. This contract is used when the issuer hires the services of a merchant who provides payment services. Keywords: Electronic Payment E-money, Maqashid Syariah